Affordable prefabricated modular houses using cement and polymer based materials and advanced design tools - Barros, Joaquim A. O. (2015)
By taking advantage of the appropriate use of cement and polymer based materials and advanced computational tools, a pre-fabricated affordable house was built in a modular system. Modular system refers to the complete structure that is built-up by assembling pre-fabricated sandwich panels composed of steel fibre reinforced self-compacting concrete (SFRSCC) outer layers that are connected by innovative glass fibre reinforced polymer (GFRP) connectors, resulting in a panel with adequate structural, acoustic, and thermal insulation properties. The modular house was prepared for a typical family of six members, but its living area can be easily increased by assembling other pre-fabricated elements. The speed of construction and the cost of the constructive elements make these houses competitive when compared to traditional solutions. In this paper the relevant research subjacent to this project (LEGOUSE) is briefly described, as well as the construction process of the built real scale prototype.